Sources of recruitment at foreign commercial banks in Jordan and their impact on the job performance proficiency - Akif Lutfi Al-Khasawneh; Nazem Mahmoud Malkawi; Abdulla Ayed AlGarni (Banks and Bank Systems, 2018)
The purpose of this study was to identify sources of recruiting as practiced by the foreign commercial banks operating in Jordan and their impact on job performance proficiency. Six foreign banks were chosen randomly, 160 questionnaires were distributed to employees from the human resource departments at these banks, 121 valid questionnaires were recovered – 76% – and statistically analyzed. Results revealed the highest level of using internal recruitment sources related to accelerating promotion. External recruitment sources related to online ads and attracting distinctive graduates. There is an impact of overall internal recruitment sources on job performance proficiency. There is no impact of the overall external recruitment sources on job performance proficiency, except external recruitment sources related to recommended employees, educational institutions, and training centers, which have impact on job performance proficiency.The study recommended to maintain the application of promotion strategies by acceleration as a source of internal employment, because they positively influence the increase in the level of performance among the employees. Maintain the follow-up of graduates at universities to attract the first of them as a source of employment, maintain contact with the training centers and select the distinguished trainees as the sources of employment, and diversify advertising methods to attract talent.